A Simple Method to Quantitate IP-10 in Dried Blood and Plasma Spots - Aabye, Martine G.; Eugen-Olsen, Jesper; Werlinrud, Anne Marie; Holm, Line Lindebo; Tuuminen, Tamara; Ravn, Pernille; Ruhwald, Morten (PLOS ONE, 2012)
Background Antigen specific release of IP-10 is an established marker for infection with M.tuberculosis. Compared to IFN-γ, IP-10 is released in 100-fold higher concentrations enabling the development of novel assays for detection. Dried blood spots are a convenient sample for high throughput newborn screening. Aim To develop a robust and sensitive ELISA-based assay for IP-10 detection in plasma, dried blood spots (DBS) and dried plasma spots (DPS); to validate the ELISA in clinically relevant samples; and to assess the performance of the assay for detection of Cytomegalovirus (CMV) and M.tuberculosis specific immune responses. Method We raised mice and rat monoclonal antibodies against human IP-10 and developed an ELISA. The assay was validated and applied to the detection of CMV and M.tuberculosis specific responses in 18 patients with immune reactivity towards M.tuberculosis and 32 healthy controls of which 22 had immune reactivity towards CMV and none towards M.tuberculosis. We compared the performance of this new assay to IFN-γ. Results The ELISA was reliable for IP-10 detection in both plasma and filter paper samples. The linear range of the ELISA was 2.5–600 pg/ml. IFN-γ was not readily detectable in DPS samples. IP-10 was stabile in filter paper samples for at least 4 weeks at 37°C. The correlation between IP-10 detected in plasma, DPS and DBS samples was excellent (r2>0.97). Conclusions This newly developed assay is reliable for IP-10 quantification in plasma, DBS and DPS samples from antigen stimulated and non-stimulated whole blood. The filter paper assays enable easy sample acquisition and transport at ambient temperature e.g. via the postal system. The system can potentially simplify diagnostic assays for M.tuberculosis and CMV infection.